Structural Health Monitoring of Large-Scale Bridges: A Synopsis of the Padma Bridge (MIST International Journal of Science and Technology, 2022)
In the recent decade, the concept of "structural health monitoring," or SHM, has gained prominence due to its promise of reflecting the condition of structures and facilitating the monitoring of their behavior. Bangladesh is a country with a long coastline, thus it is unfortunate that the SHM system has not been more widely deployed on the country's many highway bridges across rivers. Saving money on manpower, remote monitoring allows for accurate, up-to-date assessments of a bridge's structural soundness. Recent developments in sensor, communication, and storage technologies have made a worldwide SHM system for infrastructures possible. The primary goal of this investigation is to assess the performance of the structural health monitoring system on the Padma Multipurpose Bridge. Recent developments in SHM's integration with ITS show the usefulness of ITS devices (such as traffic cameras and traffic detectors) in analyzing bridge responses to multimodal traffic with varying loads or during critical events that cause excessive vibration beyond the normal limit, which can be of great assistance in tackling the Padma bridge's serviceability challenge. Integrating information from an ITS device with SHM may increase the reliability and precision of the SHM system. As a consequence of this integration, the SHM system would be less likely to misdiagnose damages (i.e., vibrations caused by big cars on a bridge may be perceived by a SHM sensor as a structural health concern of the bridge), resulting in decreased maintenance costs. This investigative study provided a summary of the SHM systems now in place for major bridges in Bangladesh, such as the spectacular Padma Bridge, and discussed their use and appropriateness in the near and far future.MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 43-55